Effects of Saline Solutions on the Desiccation Cracking and Shrinkage Behavior of Gaomiaozi Bentonite - Long Tan; Penglin Zheng; Qingbing Liu (Advances in Civil Engineering)
Bentonite, when used as buffer/backfill material in the deep disposal of high-level radioactive waste (HLW), could undergo desiccation shrinkage or even cracking due to the heat released from HLW, impairing the efficiency of the barrier system. Furthermore, in-service buffer materials are inevitably in contact with the groundwater, which sometimes contain high salt concentrations. The groundwater salinity may modify the properties of bentonite and hence affect the process of desiccation and its performance. To investigate this effect, in this study, a series of temperature-controlled desiccation tests was conducted on compacted specimens of Gaomiaozi (GMZ) bentonite preliminarily saturated with two different saline solutions (NaCl and CaCl2) at the concentration varying from 0.5 to 2.0 mol/L. The experimental results indicated that, as the concentration of saline solution increases, the initial saturated water content of bentonite decreases, whereas the residual water content at the completion of the desiccation test increases. The water evaporation rate is reduced for the specimens saturated with a high-concentration saline solution, and CaCl2 has a more significant influence on water evaporation than NaCl. The evolution of cracks on the sample surface during the desiccation process can be divided into four stages: crack growth, maintenance, closure, and stabilization; an increase in the salt concentration effectively inhibits crack development. It was shown that the infiltration of saline solutions alters the microstructure of bentonite by changing the arrangement of clay particles from a dispersed pattern to more aggregate state, which results in a decrease in shrinkage strain and shrinkage anisotropy.